Impact of Nurse Workload on Work Efficiency, Patient Safety, and Job Satisfaction: A Cross-Sectional Study - Niken Sukesi; Siti Khuzaimah Ahmad Sharoni; Rahayu Winarti; Heny Prasetyorini; Menik Kustriyani (PT.Mantaya Idea Batara, 2026)
Background: Workload is a critical determinant of nursing performance and healthcare quality, influencing work efficiency, patient safety, and job satisfaction. Despite its importance, evidence regarding these relationships remains inconsistent. This study examined the associations among workload, work efficiency, patient safety, and job satisfaction among nurses Methods: A cross-sectional study was conducted with 136 nurses. Data were collected using self-administered questionnaires and analyzed with SPSS version 26. Spearman’s rank correlation assessed associations between variables, while the Kruskal–Wallis test compared job satisfaction across workload categories. Ordinal logistic regression identified predictors of job satisfaction. Model diagnostics included assessments of multicollinearity, model fit, pseudo R², and the proportional odds assumption. Results: Workload demonstrated a weak but significant positive association with work efficiency (ρ = 0.290, p < 0.001) and a weak negative association with patient safety (ρ = −0.231, p = 0.007), but was not significantly related to job satisfaction. The Kruskal–Wallis test indicated no significant differences in job satisfaction across workload categories (p = 0.392). Ordinal logistic regression revealed that workload and work efficiency were not significant predictors of job satisfaction (p > 0.05), whereas patient safety was significantly associated with job satisfaction (p < 0.001). The model demonstrated acceptable fit (χ² = 15.452, p = 0.017), modest explanatory power (Nagelkerke R² = 0.182), no multicollinearity (VIF < 5), and satisfied the proportional odds assumption (p = 0.823). Conclusion: Overall, workload is associated with work efficiency and patient safety, although these relationships are weak. Job satisfaction appears to be more closely associated with patient safety than with workload. These findings inform workload management strategies in hospital settings and underscore the importance of strengthening patient safety culture alongside workload regulation.